The Honorific Loss in Javanese-Indonesian Movie Subtitle - Kholifah, Asrofin Nur (Language Horizon: Journal of Language Studies, 2022)
Subtitled short movies in Indonesian context allow broader and larger viewers. Bringing up less commercial issues, these kinds of movies offer somehow new insight for spectators. When it comes to subtitling, the process of transferring from the spoken to the written mode along with the different languages has always become challenge for the movie translator. The language and cultural difference between the native audience opposed to the target audience often demands translator to take the right decision to transfer. However, language and cultural baarrier persist and even it fails to accommodate. To provide the clearer depiction of this fact, this research accordingly aims to investigate the honorific loss in Javanese-Indonesian subtitle of Lemantun movie. It also explains how the Javanese honorific forms fails to be translated into Indonesian subtitle. This study is descriptive qualititative by focusing on the description of the use of honorific in Javanese subtitle and its loss in Indonesian version. The data were gathered through observation and transcription in both original and translated versions. The data were then interpreted by involving situational and social context as depicted in the screen. The result demonstrated that the honorific forms are identified through its speech level: krama (high honorific), madya (moderate) and ngoko (low) represented in different situation involving different interlocutors. In this movie, the honorific forms is used between (1) children to mother, (2) younger to older sibling, and (3) younger to the respected family member. Unfortunately, the honorific fails to transfer as a consequence of the different linguistic system and linguistc behaviour within which the language is produced. The Indonesian subtitle could not accommodate the honorific nuance as explicitly reflected in the original version. The linguistic behavior and system here become the key factors causing the transfer fails.